Translation Studies in Brahui literature - Bangulzai, Abdul lateef (Al-Burz, 2022)
Translators should have a broad understanding of the languages being used in translation​​ i.e. the language of the original text and the target language wherein the translation will be made. Thus, it is necessary that the translator should have sound knowledge and understanding of the language of the text and the translator's complete knowledge of his target language including educational, technical, practical, and linguistic skills at a mastery level. Similarly, the translator should be capable of making translation interesting and charming without losing the original essence. This article presents Maulvi Allah Bakhsh Zehri's the Handbook of Brahui Language in the 19th century with a Brahui translation of several Persian anecdotes followed by a translation from English into Brahui, titled "Brahui Reader". However, the art of translation in Brahui literature was first introduced by religious scholars and esteemed people with Arabic and Persian translations. For example. scholars of the Durkhani school of thought have been the source of many religious books, essays, commentaries, and valuable translations of the Holy Qur'an and Hadith in Brahui literature. This study discusses how the people benefited from the translations and commentaries of the Quran Majeed Furqan Hameed.